2016
DOI: 10.1111/1365-2745.12533
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of a single population can determine the vulnerability of communities to perturbations

Abstract: 1. Many aspects of global change affect the variability of species population densities, in terms of both the magnitude and pattern of density fluctuations. However, we have limited empirical understanding of the consequences of altered temporal variability of populations, independent of changes in their mean densities, for the structure and stability of natural communities and the responses of ecosystems to additional stressors. 2. We used a field experiment to test the effects of altered temporal variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 74 publications
(98 reference statements)
2
24
0
Order By: Relevance
“…We further tested the relationship between the relative abundance of dominant species and community stability. The results showed that temporal stability of protozoan community increased significantly with the relative abundance of dominant protozoan species, C. Striatum , further supporting the importance of dominant species in stabilizing communities (also see refs 12 and 19, 20, 21, 22). However, the lack of a statistically significant positive relationship between community temporal stability and dominant algal species ( S. opoliensis ) suggested that community-wide species asynchrony was more likely to play a vital role in regulating temporal stability of resident algal community.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We further tested the relationship between the relative abundance of dominant species and community stability. The results showed that temporal stability of protozoan community increased significantly with the relative abundance of dominant protozoan species, C. Striatum , further supporting the importance of dominant species in stabilizing communities (also see refs 12 and 19, 20, 21, 22). However, the lack of a statistically significant positive relationship between community temporal stability and dominant algal species ( S. opoliensis ) suggested that community-wide species asynchrony was more likely to play a vital role in regulating temporal stability of resident algal community.…”
Section: Discussionsupporting
confidence: 57%
“…In particular, the observation that resident communities receiving low-magnitude pulses were more stable than resident communities receiving high-magnitude pulses might be explained by the fact that when the pulse events continued for the entire experiment (i.e., with longer duration), there was more time for the acclimation of the dominant species to the new conditions. As a result, well-adapted dominant species with relatively stable populations could contribute significantly to community stability2122. We further tested the relationship between the relative abundance of dominant species and community stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Mrowicki et al . ). Many of the most globally important disturbances in nature are of this kind (Fig.…”
Section: The Multifaceted Nature Of Disturbances and Ecological Respomentioning
confidence: 97%
“…Directionality measures the trajectory of change, which can be highly dynamic and variable in terms of its mean and variance. Both can elicit distinct ecological responses (Bertocci et al 2005;Benedetti-Cecchi et al 2006;Garc ıa Molinos & Donohue 2010Pincebourde et al 2012;Mrowicki et al 2016). Many of the most globally important disturbances in nature are of this kind ( Fig.…”
Section: The Multifaceted Nature Of Disturbances and Ecological Respomentioning
confidence: 99%